Environmental Factors Contribute to β Cell Endoplasmic Reticulum Stress and Neo-Antigen Formation in Type 1 Diabetes - Marré, Meghan L.; Piganelli, Jon D. (Frontiers in Endocrinology, 2017)
Type 1 diabetes (T1D) is an autoimmune disease in which immune-mediated targeting and destruction of insulin-producing pancreatic islet β cells leads to chronic hyperglycemia. There are many β cell proteins that are targeted by autoreactive T cells in their native state. However, recent studies have demonstrated that many β cell proteins are recognized as neo-antigens following posttranslational modification (PTM). Although modified neo-antigens are well-established targets of pathology in other autoimmune diseases, the effects of neo-antigens in T1D progression and the mechanisms by which they are generated are not well understood. We have demonstrated that PTM occurs during endoplasmic reticulum (ER) stress, a process to which β cells are uniquely susceptible due to the high rate of insulin production in response to dynamic glucose sensing. In the context of genetic susceptibility to autoimmunity, presentation of these modified neo-antigens may activate autoreactive T cells and cause pathology. However, inherent β cell ER stress and protein PTM do not cause T1D in every genetically susceptible individual, suggesting the contribution of additional factors. Indeed, many environmental factors, such as viral infection, chemicals, or inflammatory cytokines, are associated with T1D onset, but the mechanisms by which these factors lead to disease onset remain unknown. Since these environmental factors also cause ER stress, exposure to these factors may enhance production of neo-antigens, therefore boosting β cell recognition by autoreactive T cells and exacerbating T1D pathogenesis. Therefore, the combined effects of physiological ER stress and the stress that is induced by environmental factors may lead to breaks in peripheral tolerance, contribute to antigen spread, and hasten disease onset. This Hypothesis and Theory article summarizes what is currently known about ER stress and protein PTM in autoimmune diseases including T1D and proposes a role for environmental factors in breaking immune tolerance to β cell antigens through neo-antigen formation.